Perancangan Aplikasi Pembukuan Menggunakan Metode Agile Scrum - Dhandy Joenathan Kurnia Putra; Penidas Fiodinggo Tanaem (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The product and transaction management section's business process in the Sepatu Kaki Kaki has not maximized the existing system application. This makes the business processes carried out by the store less effective. The method used in this study uses one of the agile software development models, namely Scrum. Which has advantages, including flexible requirements, speed up application production time, and require fewer team members. This research aims to produce application development that can manage products effectively and help staff analyze in accordance with the expected targets in the future. The application development uses the Kotlin programming language - Android Native, with BaaS (Backend as a Service) Firebase. The results of this research are an android application to speed up and simplify product management, the latest product stock can be known, and minimize manual recording errors.